Pemanfaatan Ai dalam Alat Pendeteksi Sampah Organik dan An-Organik: Studi Kasus Universitas Pahlawan Tuanku Tambusai - Tasya Wulandari; Tulhusna, Zilla; R. Joko Musridho; Khairunnisa; Rahmi Syafitri; Amanda Lismawati; Cindy Fatika Sari (Journal on Pustaka Cendekia Informatika, 2024)
Waste management has become an important issue in the modern era along with the increasing volume of waste generated by human activities. This study allows the use of artificial intelligence (AI) in the organic and inorganic waste detection system in the Universitas Pahlawan Tuanku Tambusai environment. The method used is a mixed method, namely a combination of quantitative approaches through questionnaires and qualitative through direct observation. The results of the study showed that 82% of respondents felt that AI increased awareness of waste management, and 91% were willing to change their waste disposal habits with this tool. Although only 23% of respondents have tried the tool, enthusiasm for this technology is quite high. This study involved academics as the main respondents, including students and cleaners, to assess the effectiveness of the tool and its impact on environmental awareness.